The money class : learn to create your new American dream - Orman, Suze (Spiegel & Grau, 2011)
Suze Orman, the woman millions of Americans have turned to for financial advice, delivers a master class on personal finance and teaches her readers that the "New American Dream" is not the things they accumulate, but the confidence that comes from knowing that which they've worked so hard for cannot be taken away from them.